Clarity: Data-Driven Automatic Assessment of Product Competitiveness - Usmani, Sheema; Bernagozzi, Mariana; Huang, Yufeng; Morales, Michelle; Sabet Sarvestani, Amir; Srivastava, Biplav (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Competitive analysis is a critical part of any business. Product managers, sellers, and marketers spend time and resources scouring through an immense amount of online and offline content, aiming to discover what their competitors are doing in the marketplace to understand what type of threat they pose to their business' financial well-being. Currently, this process is time and labor-intensive, slow and costly. This paper presents Clarity, a data-driven unsupervised system for assessment of products, which is currently in deployment in the large IT company, IBM. Clarity has been running for more than a year and is used by over 1,500 people to perform over 160 competitive analyses involving over 800 products. The system considers multiple factors from a collection of online content: numeric ratings by online users, sentiments of reviews for key product performance dimensions, content volume, and recency of content. The results and explanations of factors leading to the results are visualized in an interactive dashboard that allows users to track their product's performance as well as understand main contributing factors. Its efficacy has been tested in a series of cases across IBM's portfolio which spans software, hardware, and services.